Trends in hospitalizations for respiratory diseases in Salvador, Bahia State, Brazil, 1998-2009 Tendência das hospitalizações por doenças do aparelho respiratório no Município de Salvador, Bahia, Brasil, no período de 1998-2009 - Fernanda Pedro Antunes; Maria da Conceição Nascimento Costa; Jairnilson Silva Paim; Ligia Maria Vieira-; Carlos Antonio de Souza Teles Santos; Álvaro Augusto Cruz; Mauricio L. Barreto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Respiratory diseases are the leading cause of hospitalizations in Brazil (excluding hospital admissions related to childbirth, pregnancy, and postpartum). To analyze the trend and seasonality of hospitalizations for respiratory diseases in Salvador, Bahia State, Brazil, 1998-2009, a time trend study was performed using simple linear regression. Hospitalization rates for all respiratory diseases and specifically for asthma, chronic obstructive pulmonary disease (COPD), and pneumonia were calculated by year and age group. Hospitalizations for all respiratory diseases decreased by 45.6% (β = -2.2; p < 0.001); those due to asthma showed the largest decline (annual average 1.2/10,000), pneumonia showed the largest reduction until 2002, subsequently tending to stabilize, and COPD remained unchanged. The under-5-year age group showed the largest decline in hospitalizations for all respiratory diseases. There was no seasonality in hospitalizations for COPD. There was a reduction in the burden of hospitalizations due to respiratory diseases in Salvador, mainly due to the drop in asthma and pneumonia in children < 5 years. However, the city still has hospitalization rates for respiratory diseases that are higher than in other large Brazilian cities. As doenças do aparelho respiratório são a principal causa de hospitalizações no Brasil, excluídas as relacionadas ao parto, gravidez e puerpério. Para analisar a tendência e sazonalidade das hospitalizações por doenças do aparelho respiratório em Salvador, Bahia, 1998-2009, realizou-se um estudo de série temporal mediante regressão linear simples. Calcularam-se as taxas de internação por doenças do aparelho respiratório, asma, doença pulmonar obstrutiva crônica (DPOC) e pneumonia, por ano e grupos de idade. As hospitalizações por doenças do aparelho respiratório reduziram 45,6% (β = -2,2; p < 0,001); aquelas por asma apresentaram maior declínio (média anual de 1,2/10.000); as por pneumonia exibiram queda mais acentuada até 2002, tendendo posteriormente à estabilidade; por DPOC permaneceram inalteradas. A faixa etária < 5 anos apresentou maior queda em todas as causas de doenças do aparelho respiratório. Não houve sazonalidade nas hospitalizações por DPOC. A carga de doenças do aparelho respiratório nas hospitalizações em Salvador reduziu, principalmente, devido à asma e pneumonia em < 5 anos, mas este município ainda apresenta taxas de hospitalização por estas causas mais elevadas que outras capitais brasileiras.